SIMULASI OPTIMASI PENGUKURAN STATE OF CHARGE BATERAI DENGAN INTEGRAL OBSERVER - Asep Nugroho; Estiko Rijanto (Pusbindiklat - LIPI, 2014)
The accuracy of state of charge (SoC) measurement has been an important key in the design of Battery Management System (BMS). A SoC measurement can prevent the battery from both overcharged and undercharged condition. One of the conventional methods for SoC estimation is coloumb counting (CC). This method has a drawback regarding to the accumulation of error propagation. To improve the accuracy of CC method, the integral observer could be added. In our work charge-discharge data simulation generated by PSIM was used to test the Integral observer performance. This research used general lithium-ion battery. It was found that this approach could significantly correct the error from the numerical integral calculation and discrete data input. The error of CC method at 4000 sec was found to reach 25%; however the error propagation could be decreased up to less than <3% by Integral observer.